2004
DOI: 10.1111/j.0021-8790.2004.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the demographic determinants of population growth rate: a case study of red‐billed choughs Pyrrhocorax pyrrhocorax

Abstract: Summary 1.Identifying which age-specific demographic rates underlie variation in a population's growth rate ( λ ) is an important step towards understanding the population's dynamics. Using data from a 20-year study of marked individuals, we describe patterns of demographic variation and covariation in the Scottish red-billed chough population ( Pyrrhocorax pyrrhocorax ), and investigate which demographic rates have the greatest projected and realized influence on λ . 2. Survival, the probability of breeding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(162 citation statements)
references
References 70 publications
(216 reference statements)
7
151
4
Order By: Relevance
“…The deterministic population growth rate (l) was calculated from the dominant eigenvalue of the Leslie matrix. We validated our parameters by modelling the deterministic population trajectory correcting for newly reintroduced animals and comparing this to census data (Reid, Bignal, Bignal, McCracken & Monaghan, 2004). We used elasticities to determine which vital rates had the greatest impact on population growth (Caswell, 2001), and compared these to results from the larger, unmanaged wild dog populations examined by Creel et al (2004), which included the Selous Game Reserve in Tanzania (1991Tanzania ( -1997, Kruger National Park in South Africa (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) and Moremi Game Reserve and adjacent Wildlife Management Areas in Botswana (1989Botswana ( -2002.…”
Section: Comparison With Larger Unmanaged Populationsmentioning
confidence: 99%
“…The deterministic population growth rate (l) was calculated from the dominant eigenvalue of the Leslie matrix. We validated our parameters by modelling the deterministic population trajectory correcting for newly reintroduced animals and comparing this to census data (Reid, Bignal, Bignal, McCracken & Monaghan, 2004). We used elasticities to determine which vital rates had the greatest impact on population growth (Caswell, 2001), and compared these to results from the larger, unmanaged wild dog populations examined by Creel et al (2004), which included the Selous Game Reserve in Tanzania (1991Tanzania ( -1997, Kruger National Park in South Africa (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) and Moremi Game Reserve and adjacent Wildlife Management Areas in Botswana (1989Botswana ( -2002.…”
Section: Comparison With Larger Unmanaged Populationsmentioning
confidence: 99%
“…There is evidence that breeding success and subsequent survival of Choughs are correlated with environmental conditions before breeding on Islay (Reid et al 2003), and that survival of pre-breeders most influences the population trend (Reid et al 2004). It is possible that beneficial environmental conditions have been more frequent in recent decades, and this has resulted in population growth and colonization of new sites at the edge of their range.…”
Section: Population Trendsmentioning
confidence: 99%
“…Choughs do not breed until two or more years old (Bullock et al 1983, Reid et al 2004, usually associating with other immature birds in flocks until then (Bignal et al 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, numerous studies have shown that avian λ is more heavily influenced by first year and adult survival than by reproductive success (e.g. Saether and Bakke 2000;Reid et al 2004;Schaub et al 2006). Thus, there would be little purpose in providing supplementary food to increase reproductive success, if this demographic rate was predicted to have little impact upon λ in the target species.…”
Section: Introductionmentioning
confidence: 99%